什么时候“了liǎo” ? ：以语料探究新加坡华语口语“了” = When to liǎo? : a Corpus-based Investigation of le-particle in spoken Singapore Mandarin Chinese - Khoo, Yong Kang (2017)
目前有关普通话中助词“了”的研究不胜枚举 (如朱德熙, 1982; 刘勋宁, 1985; 郭熙, 2008; 吕叔湘, 2015)，但对新加坡华语“了”的研究仍有不足 (相关研究包括陈重瑜, 1986; 周清海和周长楫, 1998; 祝晓宏, 2015)。新加坡华语虽和普通话“了”之间有多处重叠，但有研究指出新加坡华语“了”的特点，如“了”当体标记时亦能念为liǎo。本文透过分析新加坡华语口语语料来研究 (一) 新加坡华语与普通话“了”之间的差别，及 (二) 新加坡华语le和liǎo之间的异同。本研究调查发现新加坡华语le和liǎo皆可当le1，le2和le1+2使用，但le较常当le2和le1+2使用，liǎo则更常当le2。新加坡华语也能出现在分句末修饰动宾短语。在此位置，“了”只能读为liǎo，说明liǎo和le不能随意替换使用。调查也发现新加坡华语liǎo可与le于句末共现，形成“双句末‘了’”现象。本文推论由于这两个“了”功能有所差异，读音有别，所以无法融为一体，形成这结构，而且可能已成为固定的复合句末语气词。最后，本文通过对比当代新加坡华语liǎo和汉语方言liao (如北方方言和闽南方言)，推测新加坡华语liǎo的由来和闽南方言息息相关。本文调查结果除了能够为新加坡华语的发展提供更多线索，也可为对“了”的研究带来不同的研究角度。The particle了in Mainland China Mandarin Chinese (MMC) has been extensively researched on by many linguists (e.g. Zhu, 1982; Liu, 1985; Guo, 2008; Lü, 2015). In contrast, much is left to be desired of the了le particle in Singapore Mandarin Chinese (SMC) (previous studies include Chen, 1986; Chew & Zhou, 1998; Zhu, 2015). While the two share many similarities, studies about了 in SMC point out several areas where SMC了 differs from its MMC counterpart. For instance, 了can be pronounced as le or liǎo in SMC when it used as an aspectual marker. With Spoken SMC corpus data, this study seeks to investigate (a) the differences between 了 in SMC and MMC, and (b) the differences between 了 when it is pronounced differently in SMC. Our study finds that like MMC, both le and liǎo in SMC function as le1 (perfective marker), le2 (perfect marker), and le1+2. However, le and liǎo in SMC exhibit different tendencies in functions: le tends to function as either le2 or le1+2, whereas liǎo tends to function only as le2. We also find that SMC liǎo exhibits a third distinct distribution and function (i.e. le 3) not found (and not permitted) for both MMC and SMC when the particle is pronounced as le. Instead of being a verbal suffix, 了appears in the clause-final position and follows a VO phrase. This opposes previous findings that liǎo is merely a substitution for le in SMC (Chen, 1986; Huang, 2013). Lastly, this study finds that in SMC, liǎo can co-occur with le in the form 了了 liǎo le at the sentence-final position. This study argues that liǎo le is the result of a failure in the combination of the two le-particles at the sentence-final position, and may have even been lexicalised as a new sentence-final particle. A comparison with the senses of liao in other Chinese dialects (e.g. Southern Min, see Li (2007) and Shi (2014)) reveals that these characteristics may have arose from language contact with the Southern Min dialects in Singapore. The findings of this study not only serve as a reference for studies on 了 le, but also shed light on the language variation motivated by language contact in the context of SMC.